The complete review guide to contemporary world fiction - Orthofer, M. A., 1964- (Columbia University Press, 2016)
Profiling hundreds of titles and authors from 1945 to today, with an emphasis on fiction published in the past two decades, this reference provides a fascinating portal into the styles, trends, and genres of the world's literatures, from Scandinavian crime thrillers and cutting-edge works in China to Latin American narco-fiction and award-winning French novels. Arranged by region, country, and language, entries illuminate the fiction of individual nations, cultures, and peoples, while concise biographies sketch the careers of noteworthy authors.